PENGEMBANGAN MULTIMEDIA INTERAKTIF BIOLOGI BERBASIS ONLINE UNTUK MATERI SISTEM PENCERNAAN MANUSIA DI SMA NEGERI 1 TELUK DALAM - Mercy Hatimbarasi Duha (Universitas Nias Raya, 2024)
The aim of this research is to develop online-based multimedia for learning activities. The type of research is research and development (Research and Development) with a 4-D model. There are three test stages in this research, including: validity test, practicality t test, and effectiveness test. The instruments used are questionnaires and easy test questions to determine student learning outcomes after using the product. The research results obtained through a distributed questionnaire show that online biology-based interactive multimedia is very valid, practical and effective, with a percentage of 91.05% and is suitable for use in learning. The teacher's practicalization score was 3.59 and the average practicalization score was 3.64 in the very peak category. Student motivation of 90.68 is categorized as very high. And student learning results in the cognitive domain of 87.62 indicate very good results. So, through these results, it can be concluded that the development of online-based interactive multimedia in Biology is valid, practical and effective in supporting student motivation and learning outcomes. The author's suggestions in this research are as follows: 1) For teachers, the subject can be used as an alternative learning resource to improve students' scientific abilities. 2) For other researchers who want to develop online-based interactive multimedia, it is hoped that they will carry out cognitive domain tests on students. 3) For schools, hopefully it will facilitate teachers in developing teaching materials in the form of online-based interactive multimedia. 4) For Greater Nias University, as reading material or reference for students who will compose their next scientific work.